Poly-ion complex (PIC) formation of heparin and polyamines: PIC with tetrakis (3-aminopropyl) ammonium allows sustained release of heparin. Issue 10 (October 2020) - Ito, Daichi; Ge, Dan; Kogure, Noriyuki; Manaka, Hitomi; Terui, Yusuke; Takayama, Hiromitsu; Linhardt, Robert J.; Toida, Toshihiko; Higashi, Kyohei
Abstract: Physical mixtures of cationic polymers and heparin have been developed to overcome the limitations of unfractionated heparin. In this study, we found that heparin associates with natural polyamines in water, resulting in the generation of a poly-ion complex (PIC). PIC formation (or stability) was influenced by the concentration and ratio of heparin and polyamines, molecular weight of heparin, nature of polyamines, and pH conditions. Interestingly, the PIC obtained when heparin and tetrakis (3-aminopropyl) ammonium (Taa) were mixed exhibited stability and was sticky in nature. PIC formation was due to an electrostatic interaction between heparin and Taa. Heparin-Taa PIC was administered subcutaneously to mice, and the time to maximum heparin concentration within the therapeutic range of heparin was markedly increased compared to that after a single dose of heparin. These results suggest that the quaternary ammonium structure of Taa is critical for the preparation of a stable PIC, thereby allowing the sustained release of heparin into the blood. Abstract : Poly-ion complex; Polyamine; Sustained release of heparin; Materials application; Materials characterization; Biotechnology; Pharmaceutical science; Biomedical engineering